PENGUATAN PERAN PENGASUHAN AYAH (FATHERING) DI DESA RAMAH PEREMPUAN DAN PEDULI ANAK PROVINSI JAWA TENGAH - Bagus Kisworo; Fathin Farah Fadhilah; Rina Windiarti; Rofi Wahanisa; Afdila Raudlatun Ni’mah; Rama Wahyu Arta (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The issue of fatherlessness is a serious concern in Indonesia, given the importance of fathers as partners in childcare alongside mothers. The lack of a father's involvement can trigger various negative impacts on children, such as mental health disorders, difficulty making decisions, sexual disorientation, and low self-resilience, which increases the risk of sexual violence. According to SIGA data from 2022, in Central Java, 4.37% of children experience inappropriate parenting, and 5,974 children are cared for by a single parent. PPA Symphony data recorded a surge in child violence cases from 14,446 cases in 2021 to 16,106 cases in 2022, with sexual violence as the most cases. Unfortunately, DP3AP2KB Central Java does not have a sustainable program to strengthen the role of fathers, and so far it has only been limited to movements in certain events. This research aims to provide training that emphasizes the importance of fathers' roles in parenting through materials that strengthen affective communication, regulate emotions, promote positive discipline, and encourage active involvement in children's growth and education. The results of the activity demonstrated an increase in participants' understanding of the strategic role fathers play in the family.